2015
DOI: 10.1371/journal.pone.0129108
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Time Cooling before Cryopreservation Decreased Translocation of Phosphatidylserine (Ptd-L-Ser) in Human Ovarian Tissue

Abstract: ObjectivesTo translocation (externalization) of phosphatidylserine lead at least the five negative effects observed during cells cryopreservation: hypoxia, increasing of intracellular Ca2+, osmotic disruption of cellular membranes, generation of reactive oxygen species (ROS) and lipid peroxidation. The aim of this study was to test the intensiveness of the phosphatidylserine translocation immediately after thawing and after 45 d xenografting of human ovarian tissue, which was either frozen just after operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 49 publications
7
26
0
Order By: Relevance
“…By extension, this data also suggests that a processing delay of 24 or 48 h did not cause loss of function of the vasculature and the supporting stromal cells. This finding is consistent with insight from other studies that also identified follicles in ovarian tissue xenotransplanted after a 24 h delay in cryopreservation (12,13).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…By extension, this data also suggests that a processing delay of 24 or 48 h did not cause loss of function of the vasculature and the supporting stromal cells. This finding is consistent with insight from other studies that also identified follicles in ovarian tissue xenotransplanted after a 24 h delay in cryopreservation (12,13).…”
Section: Discussionsupporting
confidence: 92%
“…Remarkably, a processing delay of 48 h resulted in a 44% decrease in the probability of follicles being graded as affected, degenerating or atretic after cryopreservation, despite showing the opposite effect in fresh tissue. This is consistent with findings from Isachenko et al who explored a 24h delay at 4°C suggesting a role for pre-cooling of human ovarian tissue before cryopreservation (13). It is possible that acclimatisation of the ovarian tissue at 4°C for 48 h provides a more gradual temperature transition, which primes the tissue to better respond to the challenges of cryopreservation and, thus, experience a reduced insult on the health of the primordial follicle pool.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, preventing translocation of phosphatidylserine (PS) to cytoplasm. Although, study have shown that when cells are exposed to oxidative stress conditions, the internally generated ROS promote the disruption of membrane asymmetrical status, causing translocation of PS [ 48 ]. This effect may translate through receptor activating signals to break mitochondrial membrane potentials and trigger the release of cytochrome C with consequent cell death via apoptosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%